Evaluating Package C Equivalency Education Policy in a Non-Formal Education Unit: A CIPP-Based Case Study from Batudaa, Gorontalo, Indonesia - Siti Ramawati Abas; Sukarman Kamuli; Sri Yulianty Mozin (International Journal of Humanities and Social Sciences Reviews, 2026)
Package C equivalency education is a strategic non-formal education policy designed to provide senior secondary education access for citizens who are not served by the formal schooling system. This study evaluates the implementation of the Package C Equivalency Education Policy at the Non-Formal Education Unit Sanggar Kegiatan Belajar in Batudaa District, Gorontalo Regency, Indonesia. The study addresses the gap between the policy objective of expanding equitable access to secondary education and the practical constraints found in local implementation. Using a qualitative evaluative case study design, the research applies the Context, Input, Process, and Product evaluation model. Data were collected through in-depth interviews, observation, and document analysis involving program managers, tutors, learners, parents, alumni, and non-formal education supervisors. The findings show that the policy is contextually relevant to learners who face economic barriers, employment demands, age constraints, and limited access to formal schooling. However, input capacity remains insufficient due to limited tutor availability, inadequate andragogical competence, insufficient learning media, and learning modules that are not yet fully contextualized. The process dimension reveals inconsistent learning schedules, lecture-dominated instruction, weak adult-learning practices, and suboptimal monitoring. Product evaluation indicates positive outcomes in graduation, academic confidence, and access to administrative requirements for work or further study, but practical skills and socio-economic impacts remain limited. The study concludes that Package C policy implementation requires stronger socialization, tutor capacity development, contextual learning resources, flexible learning management, and local policy support to generate sustainable public value.